A cross-sectional study to evaluate the correlation between blood group and split ear lobule - Pomal, Parth V.; Khilnani, Ajeet Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Cleft or split in the ear lobe can be unilateral or bilateral and various factors affect the development of split ear like wearing heavy ear ring for prolonged period of time. It may have association with blood group. Methods: The study was conducted in ENT department of a tertiary hospital of western Gujarat from July 2021 to April 2025. The 405 patients with split ear (unilateral/bilateral) were enrolled in study and blood group of all patients was assessed and tendency for split ear in particular blood group was evaluated. All patients underwent split ear lobe repair by simple suturing technique. Results: Out of total 405 patients, 137 patients had O positive blood group and 10 patients had B negative blood group. Bilateral split ear (64.44%) was more common than unilateral (35.56%). Mean age of patient was 44.79 year with standard deviation of 15.61 year. When compared with general population, where B positive accounts for 32% and O positive for 29%, while in split ear O positive blood group was the most frequently affected (34%) followed by B positive (30%), thus it did not mirror population prevalence trends. Conclusions: We did not find significant association between split ear and blood group. O positive blood group with highest number of split ears is likely due to random distribution.